Geochemistry of greenstones in theTasiusarsuaq terrane, southern West Greenland - Scherstén, Anders ; 0000-0002-2105-6172; Stendal, Henrik; Næraa, Tomas (GEUS Bulletin, 2008)
Tonalite-trondhjemite–granodiorite (TTG) gneisses and melanocratic to ultramafic greenstones dominate the Archaean basement of southern West Greenland. The greenstones are likely to represent different original environments, which is important as the mineral deposits they may host depend on this. For example, massive sulphide deposits associated with gold and base metals are commonly volcanogenic, while chrome, nickel and platinum group elements are more commonly associated with layered intrusions (Robb 2005). Current investigations by the Geological Survey of Denmark and Greenland (GEUS) in southern West Greenland are therefore focused on the origin of greenstones and their relationship to associated TTG gneisses. Here, we report on work in progress on greenstones within the Tasiusarsuaq terrane (Fig. 1; Friend et al. 1996). They differ from many other greenstone belts in southern West Greenland in their spatial association with the TTG gneisses. Unlike the Isua, Ivisârtoq and Storø greenstone belts in the central and northern Nuuk region, the Tasiusarsuaq greenstones are not proximal to terrane boundaries but form dismembered blocks and slivers within the terrane (Fig. 1). Contact relationships to the gneisses are almost exclusively tectonic, and primary textures are, with rare exceptions, obliterated by amphibolite to granulite facies metamorphism.